Phosphate Sorption in Calcareous Soils: The Role of Iron Oxide and Carbonates - UYGUR, VELI (Asian Journal of Chemistry, 2010)
Carbonate and oxides minerals in calcareous soils are known to fix large amount of phosphorus in soils. Phosphate adsorption in arid and semi arid regions' soils is very complex due to heterogenity of soil matrix, different phosphorus adsorption ability of soil components and interrelations among the soil components. In this paper equilibrium adsorption isotherms have been obtained for better understanding about the role of carbonate and iron oxides on the behaviour of phosphorus in calcareous soils with large range of carbonate and Fe-oxides content by sequential removal of relevant soil components. Statistical analysis showed that data have well conformed both Langmuir and Freundlich isotherms. After removal of soil carbonates that increased the relative content of iron oxides as compared whole soil, the amount of sorbed phosphorus considerabley decreased by 33.9-68.3 % and after removal of iron oxides some increase or decrease was observed depending on the soil characteristics. Results suggested that soil carbonates permanently affect the phosphorus adsorption, while iron oxides are to reduce phosphorus adsorption in alkaline soils of arid regions.